Kyoto classification risk scoring system and endoscopic grading of gastric intestinal metaplasia for gastric cancer: Multicenter observation study in Japan. Issue 3 (16th September 2021) - Kawamura, Masashi; Uedo, Noriya; Koike, Tomoyuki; Kanesaka, Takashi; Hatta, Waku; Ogata, Yohei; Oikawa, Tomoyuki; Iwai, Wataru; Yokosawa, Satoshi; Honda, Junya; Asonuma, Sho; Okata, Hideki; et al.
Abstract : Objectives: The usefulness of endoscopic and histological risk assessment for gastric cancer (GC) has not been fully investigated in Japanese clinical practice. Methods: In this multicenter observation study, GC and non‐GC patients were prospectively enrolled in 10 Japanese facilities. The Kyoto classification risk scoring system, the Kimura–Takemoto endoscopic atrophy classification, the endoscopic grading of gastric intestinal metaplasia (EGGIM), the operative link on gastritis assessment (OLGA) and the operative link on gastric intestinal metaplasia assessment (OLGIM) were applied to all patients. The strength of an association with GC risk was compared. In addition, important endoscopic findings in the Kyoto classification were identified. Results: Overall, 115 GC and 265 non‐GC patients were analyzed. Each risk stratification method had a significant association with GC risk in univariate analysis. In multivariate analysis, OLGIM stage III/IV (odds ratio [OR] 2.8 [95% CI 1.5–5.3]), high EGGIM score (OR 1.8 [1.0–3.1]) and opened‐type Kimura–Takemoto (OR 2.5 [1.4–4.5]) had significant associations with GC risk. In the Kyoto classification, opened‐type endoscopic atrophy, invisible regular arrangement of collecting venules (RAC), extensive (>30%) intestinal metaplasia in the corpus in image‐enhanced endoscopy, and map‐like redness in the corpus were independent high‐risk endoscopic findings. The modified Kyoto classification risk scoring system using these four findings demonstrated a better area under the receiver operating characteristic curve value (0.750, P  = 0.052) than that of the original Kyoto classification (0.706). Conclusions: The OLGIM stage III/IV, high EGGIM score and open‐typed Kimura–Takemoto had strong association with GC risk in Japanese patients. The modified Kyoto classification risk scoring system may be useful for GC risk assessment, which warrants further validation. (UMIN000027023).